Science Dialogue Mapping of Knowledge and Knowledge Gaps Related to the Effects of Dairy Intake on Human Cardiovascular Disease (P13-002-19). (13th June 2019) - Brown, Andrew; Kaiser, Kathryn; Keitt, Andrew; Allison, David
Abstract: Objectives: Dairy has been described ranging from superfood to poison, but arguments, assumptions, and data used to justify these labels are not always clear. This project used "dialogue mapping" (DMing) to extract and summarize scientific points of (dis)agreement from an expert panel. Methods: A day-long panel convened 8 experts with complimentary expertise in nutrition, obesity, and CVD. Discussions were documented through DMing, in which a meeting is summarized in real time to capture relationships among the panelists' thoughts. DMing explicitly, logically, and visually connects propositions, points, and counterpoints, even if discussed at different times, and helps identify whether experts agree and why. The map was distilled into key points and propositions (ongoing). Experts discussed two propositions: Consumption of full-fat dairy products, 1) in part because of their saturated fat levels, should be kept to a minimum for the purposes of reducing the risks of heart disease, or 2) despite their saturated fat levels, need not be kept to a minimum for the purposes of reducing the risks of heart disease. Results: A preliminary map summary shows the panel discussed several expected topics, like LDL, HDL, and contributions of dairy fat to energy intake. Other points were discussed briefly or robustly, such as specific dairy bioactives (e.g., butyrate, calcium, CLA, MCT, proteins); biobehavioral components (e.g., whether dietary fat is self-regulating); and other topics (e.g., inflammation, microbiome, microRNAs). Two evidentiary issues emerged: 1) individual variability: whether recommendations should be targeted only to those at high CVD risk; and 2) quality of evidence: whether data on CVD endpoints and dairy intake are sufficient to make reliable conclusions – positive or negative – about full-fat dairy and CVD. Several procedural improvements were identified, including using a single proposition to be supported or refuted rather than two competing propositions. Conclusions: DMing elicited a robust conversation, documenting views on topics about the relation between dairy intake and CVD. Two outstanding evidentiary concerns are: dairy-fat recommendations may need more individualization, and much long-term dairy-CVD data may not be robust enough for conclusions. Funding Sources: Dairy Management, Inc.